EFEKTIFITAS MEDIA WHATSAPP GROUP DALAM PEMBELAJARAN DARING - Khasanah Khasanah; edy nasan; Jus'aini Jus'aini (Akademika, 2021)
WhatsApp has many features for sending messages, sending images, videos, sounds, creating groups and others and is easy to operate. The purpose of this study was to determine the effectiveness of online learning using WhatsApp media during the Covid-19 emergency in the subject of Islamic Religious Education. In an effort to reduce the spread of covid-19 in schools. The research subjects were PAI subject teachers, school principals and students of class XII accounting study program. This research uses descriptive qualitative research methods. The instruments used were interviews and questionnaires in the form of questions and statements aimed at respondents. Data was collected by means of interviews and questionnaires with google form. Data analysis was performed using Milles & Huberman's interactive analysis techniques. The results showed that the application of online learning was carried out optimally in the sense that all Teaching and Learning Activities were carried out using an online system. The effectiveness of WhatsApp groups as a learning medium has not been fully effective, especially the lack of mastery of teachers in utilizing existing features. Weak supervision of students, teaching materials that students do not understand and the high cost of quotas are challenges in online learning.